Cultural Dimensions and Their Impact on Intelligent Personal Assistant Adoption in African Contexts - Shinkafi, Abdullahi A.; Bassey, Steve; Chaku, Shammah Emmanuel; Aimufua, Gilbert I. O.; Joseph, Abraham D. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
This paper investigates the influence of cultural dimensions on the adoption and user satisfaction of Intelligent Personal Assistants (IPAs) across diverse African contexts. Utilizing a sequential explanatory mixed-methods approach, data were gathered from 528 participants across West, Southern, and Central African regions through surveys and in-depth interviews. Hofstede’s cultural dimensions framework comprising power distance, individualism–collectivism, uncertainty avoidance, masculinity–femininity, and long-term orientation was applied to analyze how cultural variability shapes IPA usage behaviors and satisfaction levels. The results reveal significant differences in adoption patterns and interaction preferences, particularly influenced by collectivist values, high power distance, and heightened uncertainty avoidance. These cultural dimensions were found to moderate the relationship between perceived usefulness and user satisfaction, underscoring the importance of context-aware design. The study highlights the critical need for culturally responsive design strategies in the development of IPA interfaces tailored to African markets. This research contributes to the expanding discourse on cross-cultural technology adoption and offers practical guidance for enhancing human-computer interaction in culturally heterogeneous environments.